2014
DOI: 10.1080/10588167.2014.965606
|View full text |Cite
|
Sign up to set email alerts
|

Information-Seeking Behavior and Library Use by Distance Education Graduate Music Education Students

Abstract: During 2013, the Performing Arts Library at Kent State University conducted a survey with graduate students in the School of Music's online Master of Music in Music Education program. Eighty-tworespondents answered questions about their awareness and use of library services, non-library resources, and desired means of obtaining help, as well as their opinions about the most important services University Libraries offer. The results afforded insights into the needs, preferences, and information-seeking behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The collaboration between the traditional education model and the music online course points out the direction for the future development of education [8]. In order to further study the impact of the distance education system on education, this article will analyze the design principles and functional requirements of the distance music education system, design the structure, function and application of the system in detail, con rm the feasibility of the system, and test the system [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The collaboration between the traditional education model and the music online course points out the direction for the future development of education [8]. In order to further study the impact of the distance education system on education, this article will analyze the design principles and functional requirements of the distance music education system, design the structure, function and application of the system in detail, con rm the feasibility of the system, and test the system [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…17 Clark found that all surveyed students in an online Master's of Music in Music Education program had accessed library resources (100% used the institution's journal databases and full text, while 72% used the library's online reference databases), and that usage of Google and YouTube was 90 percent and 79 percent respectively. 18 Dougan observed that music students who used Google as a reference source were often directed to Wikipedia and other free websites. 19 According to Clark's 2013 study, important factors in resource selection include ease of access, immediate gratification, and the ability to find the exact item.…”
Section: Introductionmentioning
confidence: 99%